The urban-tech feedback loop: A surveillance and development data-walk in South Lake Union - Dillon Mahmoudi; Anthony Levenda; Alicia Sabatino (Digital Geography and Society)
In this research article, we employed an autoethnographic data-walk methodology to explore the complex relationship between urban spaces and digital data collection, using the South Lake Union neighborhood as a case study. We examined how major technology companies like Amazon, Microsoft, and various property developers leverage the dual forces of urbanization and data gathering to shape urban environments in ways that serve their interests. Our key contribution lies in uncovering the power dynamics at play, where tech companies exert significant influence over urban planning and governance, reshaping cities into spaces designed for surveillance and commodification. In areas like South Lake Union, the redevelopment into numerous small storefronts enables the granular tracking of consumer behavior, turning everyday activities into data that fuels targeted advertising and capital accumulation. We identify two central insights. First, data-walks offer a way to “story” the influence of tech corporations on urban spaces from the perspective of everyday experiences. While digital data collection is integral to capital accumulation, the process is uneven and must be viewed from various angles—including from the perspective of everyday life—to fully understand the emerging inequalities. Second, we argue that the transformation of urban environments under tech capitalism exacerbates existing social and spatial inequalities while generating new ones. The commodified surveillance of daily activities and consumption not only drives data accumulation but also reshapes the physical and social fabric of the city. This work serves as an initial step in challenging these unequal processes of surveillance-driven urban development.